Integrated Smart Agriculture, and Sustainable Tourism Model for Advancing Green Economy And Food Self-Sufficiency In Wonosalam Village - Nuryadi Nuryadi; Ony Thoyib Hadiwijaya; Koesriwulandari Koesriwulandari; Muhammad Ikhsan Setiawan; Che Zalina Zulkifli; Zulfiya Khabirova (Malikussaleh University, Aceh, Indonesia, 2026)
This study explores the integration of ecotourism and smart agriculture as a strategic approach to strengthening the green economy and achieving local food sovereignty in Wonosalam Village, Jombang Regency, Indonesia. The research develops and validates a solar-powered smart durian farming system that integrates renewable energy, precision irrigation, organic fertilization, environmental sensing, Internet of Things (IoT) technology, and artificial intelligence (AI)-based decision support. The proposed system continuously monitors key environmental parameters, including soil moisture, temperature, humidity, solar radiation, and nutrient conditions, enabling real-time recommendations for irrigation, fertilization, and crop management. A mixed-methods approach combining field observations, stakeholder engagement, system validation, and performance evaluation was employed to assess the technological, environmental, and socio-economic impacts of the integrated model. The findings demonstrate that the implementation of intelligent farming technologies significantly improves durian productivity, optimizes water and energy utilization, reduces dependence on chemical fertilizers through organic nutrient management, and enhances farm operational efficiency. Simultaneously, the integration of interactive ecotourism activities, environmental education, and digital monitoring platforms creates additional income opportunities for local communities while increasing public awareness of sustainable agriculture and biodiversity conservation. The proposed model establishes a circular rural economy by connecting agricultural production, renewable energy utilization, environmental stewardship, tourism services, and local entrepreneurship within a single integrated ecosystem. Furthermore, the system strengthens community participation, promotes technology adoption among farmers, and enhances resilience against climate variability. The study concludes that combining smart agriculture with ecotourism provides a scalable and replicable rural development framework capable of supporting national green economy strategies, decentralized food sovereignty initiatives, sustainable tourism development, and long-term environmental sustainability in agricultural regions